Biological mechanisms for the effect of obesity on cancer risk: experimental evidence - Berriel Diaz, Mauricio; Herzig, Stephan; Schafmeier, Tobias (Obesity and cancer, 2016)
Multiple epidemiological studies demonstrated that overweight and obesity significantly increase the risk of several types of cancer. As the prevalence of obesity is dramatically rising, it is expected that it will represent one of the major lifestyle-associated risk factors for cancer development in the near future. Numerous recent studies expanded knowledge about key players and pathways, which are deregulated in the obese state and potentially promote cancer initiation, progression and aggressiveness via remote and local effects. These players include (but are not limited to) insulin/IGF, adipokines and inflammatory signaling molecules as well as metabolites. Nevertheless, the detailed mechanisms linking obesity and malignant transformation at the systemic, cellular and molecular level still demand further investigation. Additionally, dysfunctional molecular metabolic pathways appear to be specific for distinct cancer entities, thereby yet precluding definition of a common principle. This chapter will present an overview of the current knowledge of molecular nodes linking obesity and cancer and will briefly touch upon potential therapy options addressing metabolic cancer etiologies.